The Role of Social Interaction in Developing Trust and Cooperation from a Social Psychology Perspective - Rahmat, Alifah; Suciati, Suciati; Hidayat, Makmur (Journal Social Humanity Perspective, 2024)
This research study looks at how social interaction affects the development of trust and cooperation in organizational environments based on a quantitative research methodology drawing on the theory of social psychology and management. The importance of trust and cooperation as described in prior scholarship has not been denied; however, there is little empirical literature characterizing the systematic organization and process of social interaction to have direct and indirect impacts on the behavior of cooperation. A sample of 200 respondents, selected by stratified random sampling among the members of completed validated Likert-scale measures created to measure social interaction, trust, and cooperation. In the data analysis, descriptive statistics, Pearson correlation, multiple regression, and mediation were embraced to probe the direct and the indirect relationships between the variables. Findings showed that social interaction is a strong predictor of trust and that trust, in interaction with social interaction is a significant predictor of cooperative behavior; trust proved to be a partial mediator, increasing the effects of social interaction on cooperation. These data provide strong quantitative support to the interaction-trust-cooperation mechanism, thus highlighting the fundamental role of relational processes in organizational performance. The current research has both theoretical and practical implications: theoretically, the research confirms the mediational value of the trust in the organizational cooperation as empirically reliable; on the practical level, the research indicates that managers should design and facilitate meaningful social interaction as a strategic asset to develop the trust and encourage the collaboration, as well as, enhance the effectual performance of teams with the aim of building strong organizational cooperation. The development of trust via systematized contact in an ever more complex and interconnected work place becomes a critical force behind the development of sustainable collaboration and organizational robustness.